Pengembangan Home Industry Melalui Digital Marketing Bersama KKN BTV UNEJ 2021 - Shinta Kristina Nugrahani; Eriska Eklezia Dwi Saputri (PEKAT: Jurnal Pengabdian Kepada Masyarakat, 2022)
The Corona Virus Disease (COVID-19) pandemic has had a major impact not only on health issues but changes in people's habits also had a national and global economic problem. Indonesia has a big focus on handling the impact of the pandemic, the decline in the number of micro-businesses is due to sales competition experienced by the community. The government's policy in dealing with the pandemic by working from home is also one of the obstacles felt by business actors. This problem is felt by all Indonesian people, including a resident who has a frozen pempek business in Gunung Anyar, Surabaya city, East Java. Through the KKN BTV UNEJ program, it is hoped that it can help develop the potential of UMKM and increase sales by utilizing digital marketing technology. It is overcome by education, training, and mentoring. Education is carried out with basic knowledge of social media, online sales techniques amid during a pandemic, creating creative content, education about effective sales by utilizing social media. Not only education is carried out but also implemented in training and assistance in product manufacture, good packaging, effective sales by utilizing social media and it is hoped that business actors can optimize sales to survive during the pandemic. Evaluation is carried out to find out the results of the work program carried out according to plan through direct discussions and interviews.